Critical Discourse in Teaching English of Speaking Skills - Saputro, Isnaini Eddy; Yulianingsih, Lilik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The application of critical discourse analysis extends beyond its usage in analyzing and observing social and political materials that are inappropriate for use in English language teaching (ELT). With the aid of the CDA, students will analyze, code, and understand textual content to enhance their speaking skills as they build arguments. This literature study examined pertinent critical discourse analysis studies released in respected journals or as conference proceedings between 2009 and 2021. After that, the papers were sorted and divided into three groups according to the following themes: (1) CDA's contributions to speaking instruction, (2) EFL learners' issues with CDA in their speaking abilities, and (3) studies on the pedagogical effects of CDA on instruction.